The dictionary of cricket - Rundell, Michael (Oxford, 1996)
The language of cricket is as complex and fascinating as the game itself. This reference to the vocabulary of the game should appeal to those well-versed in cricketing terms as well as to recent converts. It charts the evolution of the language, which reflects in turn changes in the game itself.